2013
DOI: 10.1136/tobaccocontrol-2012-050884
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behaviours and cessation services among male physicians in China: evidence from a structural equation model

Abstract: ObjectiveTo investigate smoking prevalence and cessation services provided by male physicians in hospitals in three Chinese cities.MethodsData were collected from a survey of male physicians employed at 33 hospitals in Changsha, Qingdao and Wuxi City (n=720). Exploratory factor analysis was performed to identify latent variables, and confirmatory structural equation modelling analysis was performed to test the relationships between predictor variables and smoking in male physicians, and their provision of cess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
5
21
1
Order By: Relevance
“…In fact, it is a major barrier to tobacco interventions with patients. When compared with physicians who smoke, nonsmoking physicians are more likely to identify the smoking status of their patients, provide advice on quitting and intensive cessation counseling, and initiate cessation interventions (Huang et al 2013). Last, the role model cannot be ignored.…”
Section: Addicted Health Care Professionalsmentioning
confidence: 97%
“…In fact, it is a major barrier to tobacco interventions with patients. When compared with physicians who smoke, nonsmoking physicians are more likely to identify the smoking status of their patients, provide advice on quitting and intensive cessation counseling, and initiate cessation interventions (Huang et al 2013). Last, the role model cannot be ignored.…”
Section: Addicted Health Care Professionalsmentioning
confidence: 97%
“…[33][34][35] Scientific research capacity is low. 36 India has demonstrated a commitment to the FCTC and is a world leader in the regulation of tobacco use in media and films.…”
Section: 23mentioning
confidence: 99%
“…Physician smoking status was a negative predictor of cessation success in several studies (Huang et al, 2013; Juliao et al, 2013; Ng et al, 2007; Noble, Perez Stable, & Casal, 1996; Pipe et al, 2009; Ulbricht et al, 2009), but it showed no effect on others (Gigliotti et al, 2013; Sadowski et al, 2009). Physician gender has also shown conflicting results (Frank & Harvey, 1996;Soto Mas et al, 2005; Soto Mas et al, 2008; Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, brief physician-implemented counselling interventions can increase the absolute rate of cessation by 1% to 3% (Alba, Murillo, & Castillo, 2013; Stead et al, 2013). However, despite the efforts to promote physician-led interventions for smoking cessation, few clinicians consistently implement them (Huang et al, 2013; Kruger et al, 2012; Lee et al, 2007; Pipe, Sorensen, & Reid, 2009) particularly in Latin American countries (Gigliotti et al, 2013; Juliao et al, 2013; Mejia et al, 2010). Physicians have also reported lack of training to help their patients quit and limited time for counselling during clinic visits (Perez-Stable et al, 2001; Soto Mas et al, 2005; Vogt, Hall, & Marteau, 2005; Warren, Jones, & Chauvin, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation